The Potential of Seaweed Gracilaria sp. as An Organic Waste Bioremediation Agent. - Khatimah, Khusnul; Sompa, Andi; Haerunnisa, Haerunnisa; Zaenab, St (Hasanuddin University, 2023)
Increased fishing and agricultural activities trigger eutrophication events in marine waters. Excessive availability of nutrients can cause changes in the composition of community structures in marine ecosystems. Therefore an effort is needed to mitigate the eutrophication process in coastal and marine areas by increasing the nutrient partition coefficient in compartments that can absorb or consume these nutrients such as macroalgae or seaweed. The aim of this study was to determine the absorption capacity of nutrients (N and P) from Gracilaria sp. Seaweed as a mitigating agent for eutrophication in waters. This research was conducted in October–November 2018 in a controlled manner at the PUI-P2RL Wet Laboratory, Hasanuddin University. Seaweed maintenance media is intensive pond wastewater that has gone through a filtering and sterilization process. The results showed that Gracilaria sp. able to absorb nutrients in the form of NH3, NO2 , NO3 and PO4. Gracilaria sp. able to reduce NO3 by 0.840 ± 0.065 μg/l/day, NO2 by 2.100 ± 0.609 μg/l/day, NH3 by 1.506 ± 0.204 μg/l/day and PO4 by 8.756 ± 2.785 μg/l/day.